The secret wife of Louis XIV Françoise d'Aubigné, Madame de Maintenon - Buckley, Veronica 1956- (Farrar, Straus and Giroux, 2009)
This work presents the extraordinary story of Francoise d'Aubigne, who managed to make her way from grimmest poverty to the delicate position of becoming Louis XVI's secret wife and uncrowned queen.
Includes bibliographical references and index
Keywords: Maintenon -- Madame de -- 1635-1719; Ludwig -- XIV. -- Frankreich, König -- 1638-1715; Geschichte; Favorites, Royal -- France -- Biography; Favoritin; Frankreich; France -- Kings and rulers -- Paramours -- Biography; Louis XIV -- King of France -- 1638-1715 -- Relations with women; France -- Court and courtiers -- History; France -- History -- Louis XIV, 1643-1715; Biografie